2022
DOI: 10.3390/ijerph192012987
|View full text |Cite
|
Sign up to set email alerts
|

Meanings and Experiences of End-of-Life Patients and Their Family Caregivers in Hospital-to-Home Transitions: A Constructivist Grounded Theory Study

Abstract: This study explored the meanings and experiences of patients with terminal chronic diseases and their caregivers, who face the imminence of death in the home environment after hospital discharge. The qualitative study used constructivist grounded theory. The participants were individuals with a terminal chronic illness, discharged to home, and their family caregivers. Data were gathered from in-depth interviews and field notes, and a comparative analysis was conducted to identify categories and codes, accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Two papers highlight the significant psychological challenges experienced by individuals living with advanced illnesses, including loss of control, dependence, loneliness, and feelings of abandonment. [21][22][23] Unmet psychosocial needs can have a significant impact on the well-being of both patients and their families, as reported in three studies. Unmet psychological needs lead to increased emotional distress as the condition worsens.…”
Section: Poormentioning
confidence: 89%
See 3 more Smart Citations
“…Two papers highlight the significant psychological challenges experienced by individuals living with advanced illnesses, including loss of control, dependence, loneliness, and feelings of abandonment. [21][22][23] Unmet psychosocial needs can have a significant impact on the well-being of both patients and their families, as reported in three studies. Unmet psychological needs lead to increased emotional distress as the condition worsens.…”
Section: Poormentioning
confidence: 89%
“…This uncertainty can make it difficult for patients to plan for the future, as they may not know the full extent of their condition, its long-term outcome, or the effectiveness of available treatments. [18,22,23] Given that many chronic diseases are incurable, requiring lifelong management, this review found that they are also unpredictable, leading to overwhelming fear and a loss of control. False hopes of a cure can lead to disappointment and disillusionment if the disease does not improve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide effective and efficient patient-centered care at the palliative stage, we must attend to the complexity of care and the areas of specialized interventions ( 29 ), by clearly defining the core competencies of the multidisciplinary health team members, and prioritizing a holistic and interactive approach ( 30 ). Involvement of care teams reduces hospitalization rates for PC patients and enables them to spend more time at home ( 30 ), honoring patients' wish to be cared for at home ( 31 ).…”
Section: Benefits and Implications Of Early Palliative Carementioning
confidence: 99%